Analisis Permintaan Tenaga Kerja Sektor Industri Pengolahan di Provinsi Jawa Barat Tahun 2017-2019 - Umam, Muhammad Choerul (Journal of Economics and Business, 2023)
Manufacturing industries sector is one of the sectors with the largest contribution to the economy of West Java Province. However, this condition is inversely proportional to the absorption of labor in the manufacturing industries sector which tends to be low. This study aims to the analyze influence of the district/city minimum wage, amount of unit industry, and output on the demand for labor in the manufacturing industries sector in West Java Province. The data used in this study is a combination of cross section data consist of 27 district/cities in West Java Province and 2017-2019 on time series data. The analytical method used in this study to estimate the panel data is the Fixed Effect Model (FEM). The results show that variables of the district/city minimum wage, amount of unit industry, and output simultaneously affect on the demand for labor in the manufacturing sector in West Java Province. Partially, the district/city minimum wage and variable amount of unit industry have no influence on the demand for labor in the manufacturing industries sector in West Java Province, while the variable output has a positive and significant influence on the demand for labor in the manufacturing industries sector in West Java Province.